Searching for evidence-based public policy and practice: analysis of the determinants of personal/public adaptation and mitigation behavior against particulate matter by focusing on the roles of risk perception, communication, and attribution factors - Kim, Geunsik; Kim, Seoyong; Hwang, Eunjung (International Journal of Environmental Research and Public Health, 2021)
In recent years, awareness about the risk of particulate matter (PM) has increased both domestically and internationally; consequently, various policies have been implemented to reduce PM. Since citizens are both victim and cause of this risk, PM cannot be successfully decreased only through government policies. Therefore, citizens active participation is required to reduce PM and prevent its risks. However, a theoretical model about public behavior against PM has not been established. Therefore, we suggest the public behavior model about individuals response against PM, in which response actions are classified into four types based on the combinations of the publicpersonal domains and mitigation-adaptation actions: Personal or public adaptations, and personal or public mitigations. We analyze how risk perception, risk communication, blame attribution factors influence the four types of responses against PM. The analysis results reveal that the receivers ability, negative emotion, trust in government, and age influence personal mitigation behavior, personal adaptation, public mitigation, and public adaptation, respectively. As this study demonstrates the differences in the factors influencing each type of response actions against PM, evidence-based policy is needed that considers the differences in these influencing factors.
Keywords: Air Pollutants; Communication; Government; Humans; Particulate Matter; Perception; Public Policy; Attribution factor; Blame attribution; Particulate matter; Response action; Risk communication; Risk perception